Implementation of agile approach in payroll system development: a case study on pharmacies - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research investigates the development of a payroll system in a pharmacy using an Agile approach as a solution to overcome the challenges of employee data management complexity and the need for responsiveness to business changes. The method includes three main stages: user requirements analysis, application development using the Extreme Programming (XP) method, and functional evaluation and user acceptance. The results showed that the Agile approach successfully improved the flexibility, software product responsiveness, and quality of the software satisfaction rate by 79%. The contribution of this research lies in the practical recommendations presented for developing a successful payroll system using the Agile approach, as well as highlighting the importance of adaptability and effective communication in overcoming the challenges of system development in a changing and regulated business environment. This research provides valuable insights for practitioners and researchers in understanding Agile's implementation in the payroll system development context in the pharmaceutical sector.